Émile Durkheim, his life and work a historical and critical study - Lukes, Steven (Harmondsworth Penguin, 1975)
This study of Durkheim seeks to help the reader to achieve a historical understanding of his ideas and to form critical judgments about their value. To some extent these tow aims are contradictory. On the one hand, one seeks to understand: what did Durkheim really mean, how did he see the world, how did his ideas related to one another and how did they develop, how did they related to their biographical and historical context, how were they received, what influence did they have and to what criticism were they subjected, what was it like not to make certain distinctions, not to see certain errors, of fact or of logic, not to know what has subsequently become known?
Includes indexes.
Keywords: Durkheim, Émile, 1858-1917.